2020
DOI: 10.3390/polym12020267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Methods for Cultivating Gluconacetobacter hansenii for Bacterial Cellulose and Montmorillonite Biocomposite Production: Wound-Dressing Applications

Abstract: Bacterial cellulose (BC) has received considerable attention due to its unique properties, including an ultrafine network structure with high purity, mechanical strength, inherent biodegradability, biocompatibility, high water-holding capacity and high crystallinity. These properties allow BC to be used in biomedical and industrial applications, such as medical product. This research investigated the production of BC by Gluconacetobacter hansenii ATCC 23769 using different carbon sources (glucose, mannitol, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 83 publications
0
18
0
1
Order By: Relevance
“…Any breach in the skin by wound causes invasion of microorganisms into the sensitive underneath tissues that lead to wound infection. The advanced research on wound dressing development suggests that the ideal wound dressing should provide a wet environment to the wound, absorb exudates from the wound, should be highly biocompatible, having good antimicrobial activity for quick tissue regeneration and mechanical features to remain intact [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Any breach in the skin by wound causes invasion of microorganisms into the sensitive underneath tissues that lead to wound infection. The advanced research on wound dressing development suggests that the ideal wound dressing should provide a wet environment to the wound, absorb exudates from the wound, should be highly biocompatible, having good antimicrobial activity for quick tissue regeneration and mechanical features to remain intact [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the BC membranes underwent the purification process through alkaline treatment with potassium carbonate (K 2 CO 3 ). For this purpose, the membranes were washed twice with distilled water at 80 °C for 1 h to remove impurities from the culture medium and then were treated with 0.3 mol·L −1 K 2 CO 3 aqueous solution at 80 °C for 1 h. After alkaline treatment, the BC membranes were washed with distilled water until a neutral pH (between 6.8 and 7) was obtained [ 49 ]. The purified membranes were stored at 4 °C in deionized water until further use.…”
Section: Methodsmentioning
confidence: 99%
“…However, glucose remains the most preferred nutrient source for carbon since it gets readily consumed by the bacterial cells to yield energy to meet the metabolic demands. A study conducted by Hodel et al [70] reported that G. hansenii requires six more days to produce the same value of BC (i.e., 14.72 g/l) in the mannitol modified HS medium compared to glucose modified HS medium which produces BC in only 14 days of incubation. Further, Table 1 highlights the net BC yield obtained in different mediums with different bacterial cells produced in different cultivation modes.…”
Section: Yield Of Bcmentioning
confidence: 99%
“…BC matrix with nanoporous structure and the presence of several oxygen atoms has great potential in the production of functional composites [87][88][89][90]. Reinforcement with BC in conducting materials, carbon nanotubes, ceramics, graphene oxide, and several biopolymers have been studied and proved as suitable polymeric material for industrial applications [70].…”
Section: Bc-based Biocompositesmentioning
confidence: 99%